Aplikasi Toko Online Dengan Chatbox Pada Toko KCA - Kevin Christian; Justinus Andjarwirawan; Alexander Setiawan (Jurnal Infra, 2020)
Along with the development of technology, many people are selling online. Many people who sell online in the marketplace or have a personal website to sell. But often the problem faced by sellers and consumers is ineffective communication because the media to communicate is only limited to one or two media so that consumers often become disappointed because they are waiting for a long response. To overcome this problem, an online store application is created that can make sellers and buyers communicate with several kinds of media to communicate. The feature is that the seller can receive and send messages to the seller through several social media options available, for example Whatsapp. And in order to maintain the security of buyers when transacting websites using payment gateway services from Midtrans that provide payment methods including card payments, bank transfers, direct debit, e-wallet, over the counter, and others.The end result of making this program is an online store application, which has communication features via email to social media. The conclusion obtained from making this program is that the program is feasible to use, and the store application communication features and payment can run well.